Discourse on Cultural Islam and Political Islam in the History of Indonesian Islam - Saleh, Hairus (Journal of Islamic History, 2024)
The dynamics of Cultural Islam and Political Islam still occur and are actual in people's lives today. Several Political Islam groups with their voices through Islamic parties want to make Islam the basis of ideology and Indonesia a religious state. Meanwhile, the Cultural Islam group with a missionary spirit that wants to establish Islam as life values ​​that blend with culture and also anti-sectarianism rejects the idea of ​​Political Islam. Cultural Islam holds the view that the implementation of Islamic teachings in the state does not have to be in the form of formal Islamic principles, but rather at the level of Islamic meaning and behavior in Muslim society. Cultural Islam is the middle point of the debate between political Islam and secular nationalists. This research, when viewed from the perspective of the data source, can be categorized as a literature review. If viewed from an analytical perspective, this research is considered qualitative research. Meanwhile, if we look at the purpose of conducting it, this research can be categorized as analytical descriptive research. This research aims to find out the extent of cultural Islamic discourse and political Islam in the history of Indonesian Islam.